2018
DOI: 10.3390/nano8010053
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis, Characterization and Application of Proanthocyanidins-Functionalized Gold Nanoparticles

Abstract: Green synthesis of gold nanoparticles using plant extracts is one of the more promising approaches for obtaining environmentally friendly nanomaterials for biological applications and environmental remediation. In this study, proanthocyanidins-functionalized gold nanoparticles were synthesized via a hydrothermal method. The obtained gold nanoparticles were characterized by ultraviolet and visible spectrophotometry (UV-Vis), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(43 citation statements)
references
References 42 publications
8
34
0
1
Order By: Relevance
“…9,10 Fu and coworkers found that the size distribution of proanthocyanidinfunctionalized gold nanoparticles was smaller than that of gold nanoparticles prepared using water extract. 11 Compared with polyphenols, polysaccharides have mild antioxidant properties and high stability in water. Lentinan (LNT) is soluble and biologically active biomacromolecule.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Fu and coworkers found that the size distribution of proanthocyanidinfunctionalized gold nanoparticles was smaller than that of gold nanoparticles prepared using water extract. 11 Compared with polyphenols, polysaccharides have mild antioxidant properties and high stability in water. Lentinan (LNT) is soluble and biologically active biomacromolecule.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to develop safe and economical techniques for the treatment of DDT-contaminated soil. In this respect, nanotechnology offers efficient, eco-friendly and economic solutions to rectify the problem of environmental pollution [7][8][9]. Phytochemicals, which are compounds present in plants, have different biological activities and can be used for the synthesis of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their small size, nanoparticles have a high surface area-to-volume ratio, and also exhibit excellent electrical, catalytic, optical and magnetic properties [10]. The use of metal nanoparticles for environmental clean-up is a new area of research in which only limited progress has been achieved thus far [7][8][9]. Few reports on the degradation of halocarbons by nanoparticles are available in the literature [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Spherical shaped gold nanoparticles have been prepared with juice of pomegranate [165]. The water extract of pomegranate peels have explored for the synthesis of gold nanoparticles that can act as reducing and capping agent to synthesize gold nanoparticles [166]. The peels contain portion of polyphenols and proanthocyanidins that are well known for antioxidant activity.…”
Section: Juice Mediated Biosynthesismentioning
confidence: 99%
“…The water extract yield of polyphenols and proanthocyanidins have been reported 15-20 % and 1.2-9 %, respectivey with pomegranate peels. The synthesized gold nanoparticles have been tried out for the removal of heavy metal ions and methylene blue dye from effulents [166].…”
Section: Juice Mediated Biosynthesismentioning
confidence: 99%